Parallel evolutions of morphology and magnetic properties and their attendant relationships in polycrystalline yttrium iron garnet - Nazlan, Rodziah (2012)
The parallel microstructure and magnetic-property evolutions in several polycrystalline Yttrium Iron Garnet (YIG) samples as a result of a sintering scheme were studied in detail, focusing on the attendant occurrence of their relationships: an aspect seemingly neglected, hitherto, in the garnet literature for past seven decades. Samples with nanometer sized starting powder were synthesized by employing the high-energy ball milling (HEBM) technique and then sintering toroidal compacts of the milled powder. Two batches of samples were produced for single-sample and multi-samples sintering, each covering a range of sintering temperatures from 600⁰C to 1400⁰C. The samples were characterized by transmission electron microscopy TEM), X-ray Diffraction (XRD), scanning electron microscopy (SEM), hysteresisgraph, impedance/material analyzer and picoammeter for their evolution stage in crystalline phases, microstructure, magnetic hysteresis-loop parameters,magnetic permeability components, Curie temperature and electrical resistivity respectively. With great experimental care, both the single-sample and multi-samples sintering batches yielded highly similar variation of magnetic properties versus microstructure of YIG. The results showed an increasing tendency of the saturation magnetization and saturation induction with grain size, which is attributed to crystallinity increase and to reduction of demagnetizing fields in the grains. The variation in coercivity could be related to anisotropy field changes within the samples due to grain size changes. In particular, the starting appearance of room temperature ferromagnetic order suggested by the sigmoid-shaped B-H loops seems to be dependent on a sufficient number of large enough magnetic domain-containing grains having been formed in the microstructure. Viewed simultaneously, the hysteresis loops appear to belong to three groups with different magnetism-type dominance, respectively dependent on phase purity and grain size distributions. A scrutiny of the permeability components, μ’ and μ’’, shows that there also tend to similarly belong to the above three sintering temperature related groups. The Curie temperature remained relatively stable, unaffected by the above evolutions, thus confirming its intrinsic character being dependent only on the crystal structure and compositional stoichiometry. The increased electrical resistivity while the microstructure was evolving is believed to strongly indicate improved phase purity and compositional stoichiometry.